ANALISIS YURIDIS DISKRESI KEPOLISIAN DALAM PENERAPAN DIVERSI - I KETUT SEREGIG (Law Faculty of Universitas Bandar Lampung, 2017)
The problem of diversion is often used as a legal reason for the parties involved as a suspect in a crime committed by a minor, both for the purpose of defense and in an attempt to avoid a suspect from imprisonment stipulated in the provisions of the law. Diversi as stipulated in Article 1 point 7 of Law Number 11 Year 2012, on the Criminal Justice System of the Child, is the transfer of the settlement of child cases from the criminal justice process to proceedings outside the criminal justice.In the case of the transfer of cases of perpetrators of minor offenses, there have been various perceptions or differences of legal views, especially the understanding of